Caso de aplicación: herramienta Poka Yoke en la micro y pequeña empresa Bohemian Brew Perú - Olivares Apaza, Anail Beatriz (2023)
SME (Small and Medium Enterprises) are becoming more representative in their countries; however, they do not achieve their objectives because they do not have good management, since they do not include a quality system, and they assume that this requires a high investment. Currently, the aim is to adopt Lean methodologies, generally used in large companies, so that this type of business can take advantage of its benefits. Therefore, a Poka Yoke application model is proposed to contribute to the solution of quality problems in a Peruvian brewery SME. Through the DMAIC matrix (Define, Measure, Analyze, Implement, and Control), trouble and solutions are identified, and quality indicators are reduced by more than 30%. The results show that the Lean methodology can be applied in all types of companies and that it can support entrepreneurs who have similar problems.